2012
DOI: 10.5505/tjtes.2012.89137
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic peritoneal lavage in hemodynamically stable patients with lower chest or anterior abdominal stab wounds

Abstract: AMAÇTorakoabdominal bıçak yaralanmaları bulunan ve hemodinamik açıdan stabil olan hastaların tedavisi halen tartış-malıdır. Bu çalışmada, bu tip hastalardaki tanısal peritoneal lavaj (TPL) sıvısındaki eritrosit sayısındaki optimal değer tartışıldı. GEREÇ VE YÖNTEMHemodinamik yönden stabil ve torakoabdominal bıçak yaralanması olan 388 hasta çalışmaya alındı. Laparotomi yö-nünden açık bir endikasyona sahip olmayan olgularda, peritoneal kavite 1000 cc serum fizyolojikle yıkandı ve akın-tı sıvısındaki eritrosit sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…One possibility of our lower conversion rate to operative management could be because of a combined CT and serial abdominal examination approach for our assessment rather than just single assessment, for example LWE/serial abdominal examination/CT only as noted in other studies. 4,[9][10][11][12] By reducing the number of laparotomies performed on stable patients with abdominal stab wound, this would reduce operative and post-operative complications, negative and non-therapeutic laparotomies, length of stay in hospital, use of theatre time and financial burden. Leppäniemi and Haapiainen found that there were significant financial costs associated with laparotomy and non-therapeutic laparotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility of our lower conversion rate to operative management could be because of a combined CT and serial abdominal examination approach for our assessment rather than just single assessment, for example LWE/serial abdominal examination/CT only as noted in other studies. 4,[9][10][11][12] By reducing the number of laparotomies performed on stable patients with abdominal stab wound, this would reduce operative and post-operative complications, negative and non-therapeutic laparotomies, length of stay in hospital, use of theatre time and financial burden. Leppäniemi and Haapiainen found that there were significant financial costs associated with laparotomy and non-therapeutic laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of patients who had conservative management and subsequently had operative intervention for our study is 2%, significantly lower than other trials. One possibility of our lower conversion rate to operative management could be because of a combined CT and serial abdominal examination approach for our assessment rather than just single assessment, for example LWE/serial abdominal examination/CT only as noted in other studies . By reducing the number of laparotomies performed on stable patients with abdominal stab wound, this would reduce operative and post‐operative complications, negative and non‐therapeutic laparotomies, length of stay in hospital, use of theatre time and financial burden.…”
Section: Discussionmentioning
confidence: 99%